2015
DOI: 10.1371/journal.pone.0141208
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Host-Plant Volatiles and Characterization of Two Novel General Odorant-Binding Proteins from the Legume Pod Borer, Maruca vitrata Fabricius (Lepidoptera: Crambidae)

Abstract: Chemoreception is a key feature in selection of host plant by phytophagous insects, and odorant-binding proteins (OBPs) are involved in chemical communication of both insects and vertebrates. The legume pod borer, Maruca vitrata Fabricius (Lepidoptera: Crambidae) is one of the key pest species of cowpea and widely distributed throughout tropical and subtropical regions, causing up to 80% of yield loss. In this study, we investigated the electrophysiological responses of female M. vitrata to floral volatiles fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 37 publications
7
40
0
Order By: Relevance
“…This finding suggests that OBP1 and OBP2 can detect not only sex pheromone components but also other odorants from food or plant sources, such as farnesene, farnesol, 2‐tridecanone and tetradecane, which presented higher affinities [displacement constant (Ki) <2 μM] in our earlier study (Li et al ., ). PameOBP4 , 24 , 38 and 49 were expressed equally in the antennae of both sexes, indicating that they play roles in perceiving general host volatiles, similar to the GOBPs of moths (Zhou et al ., ; Li et al ., ). For the CSPs, 10 of the 14 (71.42%) genes were expressed dominantly in the chemosensory organs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests that OBP1 and OBP2 can detect not only sex pheromone components but also other odorants from food or plant sources, such as farnesene, farnesol, 2‐tridecanone and tetradecane, which presented higher affinities [displacement constant (Ki) <2 μM] in our earlier study (Li et al ., ). PameOBP4 , 24 , 38 and 49 were expressed equally in the antennae of both sexes, indicating that they play roles in perceiving general host volatiles, similar to the GOBPs of moths (Zhou et al ., ; Li et al ., ). For the CSPs, 10 of the 14 (71.42%) genes were expressed dominantly in the chemosensory organs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we focused on one OBP ( PameOBP24 ) and one CSP ( PameCSP7 ) that were equally expressed in the antennae of both sexes and that were relatively highly expressed amongst the OBPs and CSPs based on our transcriptome data (RPKM values), which indicated that they may facilitate the detection of plant and/or food source odorants in both sexes and play key roles in the olfactory function of both sexes. The functions of the selected OBP and CSP may be like those in some of moth GOBPs, which participate in detecting common plant odorants (Liu et al ., ; Zhou et al ., ) and may be crucial for P. americana to locate different hosts. The two selected genes, PameOBP24 and PameCSP7 , were used to express recombinant proteins to further investigate their odorant affinities in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported many OBPs that are expressed in the larval stages and adult stage (Xue et al., ; Zhou et al., ). In Sclerodermus sp., OBP3 is highly expressed in the larvae, which suggests that this protein has a basic and conserved role, perhaps in feeding or identifying general volatiles (Zhou et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported many OBPs that are expressed in the larval stages and adult stage (Xue et al., ; Zhou et al., ). In Sclerodermus sp., OBP3 is highly expressed in the larvae, which suggests that this protein has a basic and conserved role, perhaps in feeding or identifying general volatiles (Zhou et al., ). Our results reveal that OBP19c, OBP44a, OBP99a , and OBP99d are expressed from the prepupa to the adult stage, which suggests their putative roles in the discrimination of mating partners and egg‐laying substrates (Zhou et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation